Has health care financial expenditure accelerated the convergence consistency of health care resource allocation efficiency in China? - Gao, Jiacheng; Liu, Yue (The Economics and Finance Letters, 2023)
This study measures the efficiency of health care resource allocation in each region of China using the global undesirable output from the Data Envelopment Analysis - Slacks Based Measure (DEA-SBM) model, on the basis of which the concept of economic convergence is introduced to analyze the convergence of health care resource allocation efficiency in China as a whole and in each region. The study found that although the overall health care resource allocation efficiency in China is relatively weakly effective, the trend is U-shaped, and since 2015, the overall health care resource allocation efficiency in China has shown an upward momentum and an overall positive performance. Second, the overall health care resource allocation efficiency in China has obvious characteristics of absolute convergence, and each region shows different degrees of absolute convergence, specifically the eastern region, which has the fastest convergence rate followed by the western region, and the central region has the slowest convergence rate. Third, after controlling for health care expenditure, the convergence rate of health care resource allocation efficiency in China as a whole and in the eastern and western regions increases to different degrees, while the convergence rate of health care resource allocation efficiency in the central region shows a small decrease.